Primer registro de Eupelmus cushmani (Crawford) (Hymenoptera: Eupelmidae) como parasitoide del barrenador de ramas del aguacate Copturus aguacatae Kissinger (Coleoptera: Curculionidae) en México - Estrada-Virgen, Mario Orlando; De Dios Á., Ndahita; Ruíz-Cancino, Enrique; Coronado-Blanco, Juana María; Rios-Velasco, Claudio; Cambero-Campos, Octavio Jhonathan (Instituto de Ecología, A.C., 2019)
Eupelmus cushmani (Crawford) (Hymenoptera: Eupelmidae) is recorded for first time as parasitoid of the avocado stem weevil (Copturus aguacatae Kissinger) in Nayarit, Mexico.